Pengaruh Transparansi dan Akuntabilitas Terhadap Loyalitas Muzakki pada Badan Amil Zakat Nasional Kabupaten Meranti - Sari, Elis Wulan; Hasanah, Nur; Bustami, Zulfahmi (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study investigated the impact of transparency and accountability on muzakki (zakat payer) loyalty at BAZNAS Kepulauan Meranti Regency, incorporating a Sharia economic perspective. Employing a quantitative descriptive approach, the research focused on a sample of 97 muzakki from a 2023 population of 3,053. Simple random sampling was utilized, with data gathered through observation, questionnaires, interviews, and documentation. Data analysis involved instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing. The findings showed transparency no significant influence on loyalty. Conversely, accountability significantly impacted loyalty. From a Sharia economic standpoint, BAZNAS's transparency aligns with the characteristics of sidiq, amanah, and fathanah, although the tabligh aspect is not fully met. Accountability, however, aligns well with Sharia economics due to its emphasis on both human-God and human-human relationships, fostering muzakki loyalty.